Knowledge and attitudes toward food sustainability among Kuwait University students - AlTarrah, Dana; Malik, Aisha; Nur, Amrizal (Frontiers in Sustainable Food Systems, 2024)
Transitioning towards sustainable food systems and sustainable diets is critical in reducing environ mental impact 14 and achieving the Sustainable Development Goals established by the United Nations General Assembly. This 15 transition requires collaborative efforts across multiple stakeholders, including the general public's knowledge and 16 attitudes. To assess the knowledge and attitudes towards food sustainability we carried out a cross-sectional study 17 among Kuwait University students with a total of 278 participants aged ≥18 years (78% females and 22% males). 18 A validated questionnaire was used for this study. Most respondents (>70%) recognized the concept of "local food" 19 and "environmental impact." The concept "green water-blue water" was least recognized among respondents 20 (75%). Participants perceived that a sustainable diet was rich in vegetables, included plenty of fresh products, and 21 was affordable. Participants (>66%) perceived a positive impact of meat and its derivatives towards sustainabil-22 ity, a misconception most common among males. Overall, participants with more knowledge about environmental 23 concepts showed favorable attitudes towards a sustainable diet. Women showed more interest in changing their 24 current dietary habits towards food sustainability. In conclusion, despite participants' positive attitude towards food 25 sustainability, lack of understanding persists, necessitating public health interventions aimed at educating con-26 sumers about sustainable diets and its impact on the environment.